Alternatif Perhitungan Struktur Atas Rangka Baja Tipe Camelback Truss Pada Jembatan Tawaeli, Palu Sulawesi Tengah - Ronaldi, Ronaldi; Sariman, Syahrul; Setiawan, Arman (Program Studi Teknik Sipil Universitas Bosowa, 2025)
As the demand for bridge infrastructure grows, efficient and effective alternatives for bridge design and analysis are essential. One such case is the Tawaeli I Bridge in Palu, Central Sulawesi, which requires careful design due to the city’s location in a high-seismic zone. The Camelback Truss steel bridge is ideal for this area because of its ability to withstand extreme conditions and provide structural stability during earthquakes. The design analysis for this type of bridge was performed using the Struktur FEM software, which evaluates bending, compression, and tension members. This analysis was validated through manual calculations. The section capacities obtained are: stringers (main longitudinal girders) IWF 500.200.11.17; cross girders (transverse girders) IWF 800.400.18.34; bottom chords (side longitudinal girders) IWF 650.650.18.34; top chords (upper members) IWF 650.650.18.34; diagonal chords (diagonal members) IWF 650.350.14.24; vertical chords (vertical members) IWF 600.200.11.17; transverse bracing IWF 250.250.9.14; diagonal bracing (wind bracing) angle 250.25.25. The mid-span deflection is 75.704 mm, within the allowable deflection of 87.5 mm. The accuracy between the Struktur FEM analysis and manual calculations is 99.9%.